IBM TS7700 release 3.3 - Coyne, Larry; Beiderbeck, Robert; Denefleh, Katja; Hew, Joe; Matsui, Sosuke; Pacini, Aderson; Schäfer, Markus; Scott, Michael; Zen, Chen (IBM International Technical Support Organization, 2016)
IBM® TS7700 is a family of mainframe virtual tape solutions that optimize data protection and business continuance for IBM z Systems™ data. Through the use of virtualization and disk cache, the TS7700 family operates at disk speeds while maintaining compatibility with existing tape operations. Its fully integrated tiered storage hierarchy takes advantage of both disk and tape technologies to deliver performance for active data and best economics for inactive and archive data. This IBM Redbooks® publication describes the TS7700 R3.3 architecture, planning, migration, implementation, and operations. The latest TS7700 family of z Systems tape virtualization is offered as two models: IBM TS7720 features encryption-capable high-capacity cache that uses 3 TB SAS disk drives with RAID 6, which can scale to large capacities with the highest level of data protection. IBM TS7740 features encryption-capable 600 GB SAS drives with RAID 6 protection. Both models write data by policy to physical tape through attachment to high-capacity, high-performance IBM TS1150 and earlier IBM 3592 model tape drives that are installed in IBM TS3500 tape libraries. Physical tape support is optional on TS7720. TS7700 R3.3 also supports external key management for disk-based encryption by using IBM Security Key Lifecycle Manager. This book intended for system architects who want to integrate their storage systems for smoother operation.
"Storage.". - "SG24-8122-03.". - Includes bibliographical references. - Online resource; title from title page (viewed June 6, 2016)
Keywords: Virtual computer systems; Virtual storage (Computer science); Data tape drives; IBM computers -- Programming; Systèmes virtuels (Informatique); Ordinateurs; Mémoires virtuelles; Lecteurs de bandes magnétiques; IBM (Ordinateurs); Programmation; tape drives; IBM computers; Programming